Capability development and management R&D professionals in a developing context, Taiwan - Hsiao, Ta-Cheng
Confucian moral values are considered with regard to their influence on personality within the R&D sector of Taiwan's industry. The study uses its own inventory, and twelve R&D institutions in Taiwan were the basis of various conclusions drawn.
This paper examines how Confucian moral values concerning personality have influenced the motivation for achievement among the dual ladder of R&D professionals in a developing context, namely Taiwan. The basic premise is that the trait of personality is a fundamental basic for achievement motivation and is influenced by the philosophical foundations and value systems of the society in which it is found. This study uses a self-developed inventory (the Confucian Personality Inventory) to identify different types of personality in order to analyze the differences among R&D professionals in Chinese society. In pursuing an investigation of professionals from twelve representative R&D institutions in Taiwan, the following conclusions were drawn : (1) One cannot neglect the cultural factors when analyzing managerial problems, especially for an old and civilized country such as China. (2) Due to Confucian influence, the Chinese value system regarding personality is quite unfavourable for exercising management of R&D institutions. (3) The Confucian personality type has an important implication for the management of R&D professionals in Taiwan.
Keywords: R&D professionals--Taiwan.